Integrated Solutions for Mine Site Closure and Management —Environmental Risk Assessment, Monitoring and Remediation - Candia, J.R.; Oblasser, A. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
The Risk Assessment and Environmental Remediation Programme of Fundación Chile has developed a toolkit for the integrated management of mine sites and mine closure, which, according to the specific needs of each case, could be applied in an independent or combined manner. This toolkit has four main stages: risk assessment (1st stage), monitoring (2nd stage), remediation and treatment (3rd stage), and processing and analysis (4th stage). The aim of this article is to describe the methodology and basic applications of the toolkit.